Notes on Sumerian Lexicography, II - Civil, M.
copy Bryn Mawr (unnumbered) and CBS 7269; GÁN(-ga) = ašax(-ga); imtu-ru-na, imdurun-na, imdu5-ri-na, ti/tu-nu-ur, du-ru-na/un, di-li- nа/im, dili-en/na, šu-rin-na “oven”.